Studi Pembuatan Minuman Instan Alpukat (Persea americana) Dengan Penambahan Gula Semut - Olivia Lois; Abdul Halik; Fatmawati Fatmawati (Fakultas Pertanian Universitas Bosowa, 2026)
Instant powdered drinks are products with quite low water content, namely around 0.6-0.85% through certain processing processes, and do not affect the content or efficacy of food ingredients. Brown sugar is crystallized palm sugar. Avocados contain vitamins A, C, E, K, vitamin B6, thiamine, riboflavin, niacin, and magnesium. This research aims to determine the best addition of ant sugar in making instant drinks and to determine the effect of adding ant sugar on water content, sugar content, and organoleptic tests (color, aroma, and taste) in instant avocado drinks. The research treatment was the addition of ant sugar (30%, 35%, 40%, 45%) and 40% avocado meat (constant). Research parameters for water content, sugar content, organoleptic tests for color, aroma, and taste. Data analysis used the Completely Randomized Design (CRD) method, with four treatment levels and three replications. The observation data was analyzed using diversity (ANOVA) with a follow-up test using the Least Significant Difference (BNT) test. The best results obtained from adding ant sugar were found in the treatment of adding 40% ant sugar in terms of water content 3.9%, sugar content 48.71%, color 3.02 (like), aroma 2.85 (like), and taste 2.74 (suka). The water content produced in this research does not meet SNI 01-4320-2004. Meanwhile, the sugar content of instant avocado drinks meets the requirements of SNI-4320-2004. Minuman serbuk instan merupakan produk dengan kadar air yang cukup rendah yaitu sekitar 0.6-0.85% melalui proses pengolahan tertentu, dan tidak mempengaruhi kandungan atau khasiat dalam bahan pangan. Gula semut (Brown sugar) adalah gula merah palma (palm sugar) yang dikristalkan. Alpukat memiliki kandungan vitamin A, C, E, K, vitamin B6, tiatamin, riboflavin, niasin, dan magnesium. Penelitian ini bertujuan untuk mengetahui penambahan terbaik gula semut pada pembuatan minuman instan dan untuk mengetahui pengaruh penambahan gula semut terhadap kadar air, kadar gula, dan uji organoleptik (warna, aroma, dan cita rasa) pada minuman instan alpukat. Perlakuan penelitian yaitu penambahan gula semut (30%, 35%, 40%, 45%) dan daging alpukat 40% (konstan). Parameter penelitian kadar air, kadar gula, uji organoleptik warna, aroma, dan cita rasa. Analisis data digunakan metode Rancangan Acak Lengkap (RAL), dengan empat taraf perlakuan dan tiga kali ulangan. Data hasil pengamatan dianalisis menggunakan keragaman (ANOVA) dengan uji lanjutan yang digunakan uji Beda Nyata Terkecil (BNT). Hasil terbaik diperoleh pada penambahan gula semut terdapat pada perlakuan penambahan gula semut 40% ditinjau dari kadar air 3.9%, kadar gula 48.71%, warna 3.02 (suka), aroma 2.85% (suka), dan cita rasa 2.74 (suka). Kandungan kadar air yang dihasilkan dalam penelitian ini tidak memenuhi SNI 01-4320-2004; sedangkan, kandungan kadar gula minuman instan alpukat memenuhi syarat SNI 01-4320-2004.